Questioning God - Caputo, John D.; Dooley, Mark; Scanlon, Michael J. (Indiana series in the philosophy of religion, 2001)
In 15 insightful essays, Jacques Derrida and an international group of scholars of religion explore postmodern thinking about God and consider the nature of forgiveness in relation to the paradoxes of the gift. Among the themes addressed by contributors are the possibilities of imagining God as unthinkable, imagining God as non-patriarchal, imagining a return to Augustine, and imagining an age in which praise is far more important than narrative. Questioning God moves readers beyond the parameters of meta